On the energy budgets of fragmenting rockfalls and rockslides: Insights from experiments. Issue 7 (21st July 2016) - Haug, Øystein Thordén; Rosenau, Matthias; Leever, Karen; Oncken, Onno
Abstract: The travel lengths of rockfalls and rockslides can be difficult to predict due to complex interactions of numerous physical processes, such as fragmentation of the rock mass and its effect on the energy dissipation through basal and internal friction. Previous studies have shown that the front of the rockslide deposits travels farther with increased fragmentation. However, little is known about the displacement of the center of mass, which is the relevant parameter for studying the energy budget, leaving open the question whether fragmentation acts as an effective sink or source of energy. Taking advantage of a newly developed rock analogue material, we perform a total of 109 experiments to study the effect of fragmentation on the displacement of the center of mass and the energy budget of experimental rockslides. To determine the degree of fragmentation, we define a characteristic fragment size from the total mass of the experimental sample and the mass of the largest fragment. The degree of fragmentation is seen to depend linearly on the aspect ratio of the experimental sample and as a power law on its cohesion. Similar to the previous studies, our results show that the travel distance of the front of the deposits increases with the degree of fragmentation. In contrast, displacement of the center of mass is reduced with the degree of fragmentation, suggesting increased energy consumption, consistent with the assumption that fragmentation acts effectively as an energy sink. Key Points: We study fragmenting rockslides and rockfalls using a new rock analogue material With an increased fragmentation, the front of the deposits travel farther, but the center of mass travels shorter The experimental results show that fragmentation acts as an effective energy sink